Estimating the costs of tsetse control options: An example for Uganda - Shaw, A.P.M.; Torr, S.J.; Waiswa, C.; Cecchi, G.; Wint, G.R.W.; Mattioli, R.C.; Robinson, Timothy P. (Elsevier, 2013)
Decision-making and financial planning for tsetse control is complex, with a particularly wide range of choices to be made on location, timing, strategy and methods. This paper presents full cost estimates for eliminating or continuously controlling tsetse in a hypothetical area of 10,000 km2 located in south-eastern Uganda. Four tsetse control techniques were analysed: (i) artificial baits (insecticide-treated traps/targets), (ii) insecticide-treated cattle (ITC), (iii) aerial spraying using the sequential aerosol technique (SAT) and (iv) the addition of the sterile insect technique (SIT) to the insecticide-based methods (i–iii). For the creation of fly-free zones and using a 10% discount rate, the field costs per km2 came to US$283 for traps (4 traps per km2), US$30 for ITC (5 treated cattle per km2 using restricted application), US$380 for SAT and US$758 for adding SIT. The inclusion of entomological and other preliminary studies plus administrative overheads adds substantially to the overall cost, so that the total costs become US$482 for traps, US$220 for ITC, US$552 for SAT and US$993 – 1365 if SIT is added following suppression using another method. These basic costs would apply to trouble-free operations dealing with isolated tsetse populations. Estimates were also made for non-isolated populations, allowing for a barrier covering 10% of the intervention area, maintained for 3 years. Where traps were used as a barrier, the total cost of elimination increased by between 29% and 57% and for ITC barriers the increase was between 12% and 30%. In the case of continuous tsetse control operations, costs were estimated over a 20-year period and discounted at 10%. Total costs per km2 came to US$368 for ITC, US$2114 for traps, all deployed continuously, and US$2442 for SAT applied at 3-year intervals. The lower costs compared favourably with the regular treatment of cattle with prophylactic trypanocides (US$3862 per km2 assuming four doses per annum at 45 cattle per km2). Throughout the study, sensitivity analyses were conducted to explore the impact on cost estimates of different densities of ITC and traps, costs of baseline studies and discount rates. The present analysis highlights the cost differentials between the different intervention techniques, whilst attesting to the significant progress made over the years in reducing field costs. Results indicate that continuous control activities can be cost-effective in reducing tsetse populations, especially where the creation of fly-free zones is challenging and reinvasion pressure high.